Gaya hidup penderita diabetes mellitus Tipe 2 pada masyarakat di daerah perkotaan - Febriyan, Heironimus Billy (Wellness And Healthy Magazine, 2020)
Diabetes Mellitus Type 2 is a disease characterized by high glucose levels in the blood exceed the standard value. The condition causes the disruption of the function of organs, causing all sorts of problems, among others such as eye disorders, heart, healing wounds, and stroke. Diabetes mellitus type 2 has some risk factors such as gender, age, family history, diabetes, obesity, hypertension, dyslipidemia, less activity, fat and carbohydrate intake high. The residence also can be a risk factor for type 2 diabetes mellitus where urban areas are associated with a change in lifestyle and dietary habits compared with the countryside. It became one of the causes of the increase in type 2 diabetes mellitus in urban areas. Conclusion It was found that type 2 diabetes mellitus is very influential, especially in decreased quality of life, especially in urban areas.